Reflection coefficient of low energy light ions based on the theory of ion ranges - Vukanić Jovan (Nuclear Technology and Radiation Protection, 2007)
Multiple collision theory of light ion ranges in an infinite medium has been used to calculate reflection coefficient from penetration profile in the energy region where the electronic stopping is dominating and proportional to the ion velocity. Ion-target atom collisions are determined by the inverse square scattering potential. The Gaussian approximation of a penetration profile as well as reflection coefficient are found in the form of analytic formulas. Corrections for multiple crossings of the surface have been applied. The results are compared with those from our previous calculations on the basis of DP0 solution of the transport equation and with the computer simulation data.